#Scanners: integrating physiology into cinematic experiences - Pike, Matthew; Ramchurn, Richard; Wilson, Max L. (ACM, 2015)
In this paper we present #Scanners, a digital arts installation that aims to bridge the gap between digital arts and neuroscience. #Scanners is an experience in which an individual wears a wireless brain scanners whilst being presented media which is dynamically affected by the individuals physiology. A prototype system has been successfully trialled on roughly 100 users over the past 18 months and has received unanimously positive feedback. We state the minimal additional requirements for demonstrating a Higher Fidelity prototype system and argue the value of including #Scanners at C&C2015.